Effectiveness of an electronic health record-data warehouse system implementation: return on investment analysis. (2017) - Muriana, Cinzia; Vizzini, Giovan Battista; Piazza, Tommaso; Gilia, Giulio; Mistretta, Vincenzo
Electronic health records (EHRs) allow the storing of a patient's history, and retrieval of information. Despite studies have pointed out the impact of EHRs in reducing healthcare structures' costs and increasing revenues, it is not clear if the return on investment (ROI) justifies the initial effort required. This paper proposes an advanced EHR joined to a data ware house (DWH) enabling business intelligence analysis, for structuring documents and manipulating atomic data. A case study is presented dealing with the implementation of a prototypal version of the EHR-DWH developed within the Smart Health 2.0 project (PON04a2_C), carried out between 2012 and 2015, at IRCCS-ISMETT, an Italian transplant institute. The ROI, the pay-back period, and the net present value have been calculated based on actual investment costs, and estimated maintenance costs. Results show that the ROI is in line with that of the reference sector, making profitable investments in EHRs.